Parental leave policy for ophthalmology residents: Results of a nationwide cross-sectional study of program directors - Wang, Kendrick (J Surg Educ, 2020)
BACKGROUND: Many residents become parents during residency and the adequacy of parental leave is integrally related to resident wellness. OBJECTIVE: To understand current parental leave policies in ophthalmology residency programs and program director perceptions of the impact of parental leave on trainees. DESIGN: Cross-sectional study. SETTING: Multi-center among all U.S. ophthalmology residency programs. PARTICIPANTS: Ophthalmology residency program directors during the 2017–2018 academic year. RESULTS: Sixty-eight percent (82/120) program directors participated in this study. The majority of programs had written maternity leave policies (89%) and partner leave policies (72%). The typical duration of maternity leave taken ranged from 4–6 weeks while typical partner leave duration taken ranged from 1 day to 2 weeks. Residents who take leave may need to extend training at 72% of programs. Program directors perceived that parental leave negatively impacts resident scholarly activities and surgical skills and volume. Male program directors, relative to female program directors, perceived that becoming a childbearing parent negatively impacts resident dedication to patient care. Program directors raised concerns including local support and policy, extension of residency, impact on residents, impact on programs, consistency and fairness, and desire for national policy change. CONCLUSIONS: Parental leave practices vary significantly among ophthalmology training programs with residents typically taking less leave than permitted. Program directors are challenged to accommodate parental leave while balancing resident training and wellness for all trainees in their program.